A Simple Intraoperative Technique for Restoring Rotational and Length Alignment After Distal Femur Resection and Endoprosthesis Reconstruction: A Technical Note - Ramy Samargandi, MD; Louis-Romée Le Nail, PhD (Arthroplasty Today, 2024)
Restoring femoral rotation alignment and limb length after distal femur resection and endoprosthetic reconstruction is crucial to avoid poor outcomes. This technical note presents a simple and reliable intraoperative technique for restoring femoral rotation and length during distal femur resection and endoprosthetic reconstruction without the need for extensive preoperative planning or complex perioperative modalities. The method utilizes an external fixator frame as a guiding device to assess and restore the native alignment. This approach provides a practical alternative to relying solely on the position of the linea aspera, which has been shown to be an unreliable landmark for rotational alignment. Implementing this technique can contribute to improved functional outcomes in patients undergoing distal femur endoprosthetic reconstruction.